Application of synthetic pig iron in production of electric burners - D. A. Khudokormov; A. G. Slutsky; V. A. Kishkevich (Литьë и металлургия)
The article shows possibility of use of high-duty cast iron in production of heaters elements. The authors give recommendations which allow to produce this high-duty cost iron at the lowest costs.